Sequence stratigraphic framework for mixed aeolian, peritidal and marine environments: Insights from the Pennsylvanian subtropical record of Western Pangaea. Issue 7 (21st June 2016) - Blanchard, Sébastien; Fielding, Christopher R.; Frank, Tracy D.; Barrick, James E.
Abstract: Due to difficulties in correlating aeolian deposits with coeval marine facies, sequence stratigraphic interpretations for arid coastal successions are debated and lack a unifying model. The Pennsylvanian record of northern Wyoming, USA, consisting of mixed siliciclastic–carbonate sequences deposited in arid, subtropical conditions, provides an ideal opportunity to study linkages between such environments. Detailed facies models and sequence stratigraphic frameworks were developed for the Ranchester Limestone Member (Amsden Formation) and Tensleep Formation by integrating data from 16 measured sections across the eastern side of the Bighorn Basin with new conodont biostratigraphic data. The basal Ranchester Limestone Member consists of dolomite interbedded with thin shale layers, interpreted to represent alternating deposition in shallow marine (fossiliferous dolomite) and supratidal (cherty dolomite) settings, interspersed with periods of exposure (pedogenically modified dolomites and shales). The upper Ranchester Limestone Member consists of purple shales, siltstones, dolomicrites and bimodally cross‐bedded sandstones in the northern part of the basin, interpreted as deposits of mixed siliciclastic–carbonate tidal flats. The Tensleep Formation is characterized by thick (3 to 15 m) aeolian sandstones interbedded with peritidal heteroliths and marine dolomites, indicating cycles of erg accumulation, preservation and flooding. Marine carbonates are unconformably overlain by peritidal deposits and/or aeolian sandstones interpreted as lowstand systems tract deposits. Marine transgression was often accompanied by the generation of sharp supersurfaces. Lags and peritidal heteroliths were deposited during early stages of transgression. Late transgressive systems tract fossiliferous carbonates overlie supersurfaces. Highstand systems tract deposits are lacking, either due to non‐deposition or post‐depositional erosion. The magnitude of inferred relative sea‐level fluctuations (>19 m), estimated by comparison with analogous modern settings, is similar to estimates from coeval palaeotropical records. This study demonstrates that sequence stratigraphic terminology can be extended to coastal ergs interacting with marine environments, and offers insights into the dynamics of subtropical environments.